Smart Anticancer Nanofibers: Hyperthermia Nanofiber Platform Synergized by Sustained Release of Paclitaxel to Improve Antitumor Efficiency (Adv. Healthcare Mater. 13/2019). Issue 13 (11th July 2019) - Niiyama, Eri; Uto, Koichiro; Lee, Chun Man; Sakura, Kazuma; Ebara, Mitsuhiro
Abstract : In article number 1900102, Mitsuhiro Ebara and co‐workers demonstrate the antitumor effect of a nanofiber mesh that can deliver heat and antitumor drugs in a controlled manner. The mesh generates heat when the loaded magnetic particles are activated in a magnetic field. The thermochemotherapy combination displays enhanced antitumor activity and the systemic toxic effects can be eliminated due to local release of the chemotherapeutic agents.